Evaluation of the effect of methylprednisolone and N-acetylcystein on anastomotic degeneration and regeneraton of the facial nerve - Karlidag, Turgut; Yildiz, Mucahit; Yalcin, Sinasi; Colakoglu, Neriman; Kaygusuz, Irfan; Sapmaz, Emrah (Elsevier Sci Ltd, 2012)
Objectives: This study was aimed to determine the effects of methylprednisolone and N-acetylcystein on nerve healing in facial nerve anastomosis. Methods: Thirty rabbits were randomly divided into 3 groups: Group I: control group received no medication; Group II: 50 mg/kg/day Nacetylcystein administered group; Group III, I mg/kg/day Methylprednisolone administered group. All rabbits underwent the same standard surgical procedure. A 1 mm segment was resected from the facial nerve and the free ends were anastomosed. The drugs were administered for two months twice a day. At the end of the second month, the anastomosed regions were dissected and examined under electron and light microscopy. Results: Best nerve regeneration was observed in the N-acetylcystein and the control groups, respectively, whereas the weakest regeneration was determined in the methylprednisolone group. In the N-acetylcystein group, due to Schwann cell and glial cell proliferation, the increased regeneration rate was significantly higher compared to that of the methylprednisolone group. In the methylprednisolone group, no significant regeneration was observed despite the presence of degenerative signs of significant axonal withdrawal and an increase in the number of myelin debris. Conclusion: In the present study, we demonstrated that methylprednisolone had no beneficial effect in nerve regeneration after facial nerve anastomosis. It further caused increased degeneration. On the contrary, N-acetylcystein administration significantly increased the extent of regeneration, whereas it decreased the extent of degeneration compared to the control and the methylprednisolone groups. Crown Copyright (C) 2011 Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: Facial nerve anastomosis; Methylprednisolone; N-Acetylcystein; Trauma